Evaluation of a Trunk Supporting Exoskeleton for reducing Muscle Fatigue. (November 2019) - Poon, Nathan; van Engelhoven, Logan; Kazerooni, Homayoon; Harris, Carisa
Although the effect of wearing a back-support exoskeleton during lifting has been demonstrated to reduce overall muscle activation, less is known about how wearing exoskeletons affect muscular fatigue and oxygen consumption. The purpose of this study is to evaluate the effect of wearing a back-support exoskeleton (backX) on muscle fatigue during repetitive lifting by assessing whether wearing backX increases endurance time relative to lifting unassisted. A secondary objective of this study is to quantify changes in oxygen consumption rate while performing a repetitive lifting task with and without backX to address a common industry concern. The UC Ergonomics Lab evaluated backX on twelve male subjects by measuring bilateral muscle activity of the erector spinae and oxygen consumption rate. Summary measures of muscle activity for 50 and 90 percent of the repetitive lifting session were used to characterize peak and mean muscle activity. Oxygen consumption rate was collected continuously during the repetitive lifting session. Compared to the unassisted condition, wearing backX reduced peak lumbar erector spinae activation by 16.5% and 21.8% (p < 0.05). The time subjects could hold a back-straining posture after the repetitive lifting session increased by 52% after wearing backX during the lifting task. The was no significant negative change in oxygen consumption rate. This study confirms that wearing a backX reduces muscle activation in the lower back for this specific dynamic lifting task. Additionally, we find that wearing a backX may reduce the risk of low back injuries by reducing muscle activity and increasing endurance time to fatigue